2022
DOI: 10.3390/su14095522
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects of City–County Mergers in China: Strengthening Governance or Aggravating Pollution?

Abstract: Green and high-quality development is the focus of China’s urban development strategy in the new era. The city–county merger policy has been one of several powerful tools used by the Chinese government to promote urbanization in recent decades, but whether and how it influences the environment has been rarely discussed. Using the multi-period difference-in-differences method and urban panel datasets, we investigated the environmental effects of the city–county merger policy in China from 2000–2016 and obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…From the perspective of land urbanization, current studies have shown that there is a positive in-teraction between land resource integration and industrial structure [37]. Therefore, the promotion of urbanization will drive the change in social consumption and daily life, push the reorganization of consumption structure [38], propel the transformation of industrial structure [39], and increase the overall strength of the region [40,41]. With the progress of population urbanization, individuals' sense of relative exploitation decreases, and life satisfaction will increase [2,3].…”
Section: Population Urbanization and Life Satisfactionmentioning
confidence: 99%
“…From the perspective of land urbanization, current studies have shown that there is a positive in-teraction between land resource integration and industrial structure [37]. Therefore, the promotion of urbanization will drive the change in social consumption and daily life, push the reorganization of consumption structure [38], propel the transformation of industrial structure [39], and increase the overall strength of the region [40,41]. With the progress of population urbanization, individuals' sense of relative exploitation decreases, and life satisfaction will increase [2,3].…”
Section: Population Urbanization and Life Satisfactionmentioning
confidence: 99%
“…The urbanization of the population due to the reform of county-to-district is attributed to the integration of markets and the agglomeration effect of the economy, and to measure the effect of the agglomeration of the economy, the variable economic intensity (EI) = GDP per capita× population density = GDP/urban area is introduced. Column (6) shows that the economic agglomeration of cities is promoted by the reform of county-to-district and when the economic intensity and reform variables are added to the model and the population density is regressed simultaneously, the results are shown in column (7), and compared with column (1), although the significance of the reform variable does not decrease, the reform coefficient is significantly reduced, indicating that the economic agglomeration of cities after the reform of county-to-district contributes to the population agglomeration of cities. This means that "people follow industry".…”
Section: Mechanism Analysismentioning
confidence: 99%
“…Few scholars directly answer the above question through reliable empirical analysis. Cao et al (2022) found that the merger of cities and counties can improve the level of centralized management, such as finance and environmental governance, thereby reducing urban PM2.5 emissions [7]. The city's PM2.5 is only part of the city's pollution.…”
Section: Introductionmentioning
confidence: 99%